Familial campomelic dysplasia due to maternal germinal mosaicism. (2nd April 2018) - Higeta, Daisuke; Yamaguchi, Rie; Takagi, Takeshi; Nishimura, Gen; Sameshima, Kiyoko; Saito, Kayoko; Minegishi, Takashi
ABSTRACT: Campomelic dysplasia is an autosomal dominant skeletal dysplasia caused by heterozygous SOX9 mutations. Most patients are sporadic due to a de novo mutation. Familial campomelic dysplasia is very rare. We report on a familial campomelic dysplasia caused by maternal germinal mosaicism. Two siblings showed the classic campomelic dysplasia phenotype with a novel SOX9 mutation (NM_000346.3: c.441delC, p.(Asn147Lysfs*36)). Radiological examination of the mother showed mild skeletal changes. Then, her somatic mosaicism of the mutation was ascertained. This is the first report of molecularly confirmed maternal germinal mosaicism for a SOX9 mutation. We suggest that a meticulous clinical examination of the parents, even if they are superficially healthy, is needed to avoid overlooking germinal mosaicism of SOX9 mutations.